#TITLE_ALTERNATIVE# - FEBRIDIYANSYAH (NIM : 10207026); Pembimbing : Dr.rer.nat. Sparisoma Viridi; Prof. Dr.Eng. Mik, REZHA
In this final project, the traffic process in one-line streets examined using a model that relates velocity of two vehicles in a row, the distance between vehicles, vehicle acceleration and a free variable. This model can be used to determines the vehicle velocity and the result can be compared to the velocity of observations. The results of modeling indicate value is 0.0111, and the vehicle velocity (model) approaches of vehicle velocity (observations).